Ironia verbal: marcas, funcionamento, efetivação e absurdo - https://doi.org/10.21680/1983-2435.2022v7n2ID29865; https://orcid.org/0000-0001-7352-2334; Wendell Pereira da Silva (Revista Odisséia, 2022)
Verbal irony is the subject of numerous scientific research in the field of language studies, with no consensus as regards its specificities, namely concerning its nature and its marks or textual indexes. In this article, we debate the functioning of irony and the resources mobilized for its fulfillment and detection. To this end, we adopted the studies by Ducrot (1987), Maingueneau (1997), Muecke (2008), Guimarães (2001) and Attardo (2000) as a theoretical framework, with the corpus consisting ofA modest proposal and other satirical texts, by Swift (2005); an excerpt by Montesquieu (apud Maingueneau, 1997); and Cuca fundida, by Allen (2013). As a preliminary result, we anticipate that the verbal irony presupposes the assumption of an absurd enunciator (or point of view) and the discretionary nature of its would-be intrinsic marks.